2014
DOI: 10.1080/13102818.2014.945237
|View full text |Cite
|
Sign up to set email alerts
|

Antiviral activity ofBifidobacterium adolescentisSPM1605 against Coxsackievirus B3

Abstract: Bifidobacteria are considered one of the most beneficial probiotics and have been widely studied for their effects against specific pathogens. The present study investigated the antiviral activity of probiotics isolated from Koreans against Coxsackievirus B3 (CVB3). The effect of probiotic isolates against CVB3 was measured by the plaque assay and cellular toxicity of bifidobacteria in HeLa cells was measured using 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Among 13 probiotic iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 30 publications
1
25
0
4
Order By: Relevance
“…Lactobacillus casei metabolites behaviour showed that the percentage of positive NSP4 cells were the same as those of the positive control, implying that the virus was being replicated inside of the cells in the same proportion of the population of the positive control; regardless, NSP4 amount was significantly lower when compared with the positive control, suggesting that the metabolite might be interfering with any step of the viral cycle affecting the amount of intracellular NSP4 produced as previous authors report the effect of probiotics within viral proteins production or gene expression Lee et al 2013a;Kim et al 2014). On the other hand, the percentage of Ca +2 positive cells was the same as the positive control, as it was expected; but the amount of intracellular Ca 2+ was significantly decreased in comparison with the positive control; which agreed with the NSP4 behaviour (Table 1).…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations
“…Lactobacillus casei metabolites behaviour showed that the percentage of positive NSP4 cells were the same as those of the positive control, implying that the virus was being replicated inside of the cells in the same proportion of the population of the positive control; regardless, NSP4 amount was significantly lower when compared with the positive control, suggesting that the metabolite might be interfering with any step of the viral cycle affecting the amount of intracellular NSP4 produced as previous authors report the effect of probiotics within viral proteins production or gene expression Lee et al 2013a;Kim et al 2014). On the other hand, the percentage of Ca +2 positive cells was the same as the positive control, as it was expected; but the amount of intracellular Ca 2+ was significantly decreased in comparison with the positive control; which agreed with the NSP4 behaviour (Table 1).…”
Section: Discussionmentioning
confidence: 60%
“…The reduction of the protein could be seen in the experimental population as well, taking into account that the percentage of NSP4 positive cells was also decreased compared with the positive control, suggesting an efficacious antiviral effect, carrying out an inhibitory effect during the viral cycle and cellular damage. Once again is being reported an antiviral activity of a B. adolescentis strain, that compared with previous reports, other strains of this micro-organism, already had antiviral activity against other viruses by different mechanisms of action Cha et al 2012;Lee et al 2013a;Kim et al 2014).…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Alternative method of antiviral agents is suggested application of probiotic bacteria (Chai et al, 2013;Kwak et al, 2013;Lee et al, 2013;Kim et al, 2014;Lehtoranta et al, 2014). Probiotics are live microorganisms which when administered in adequate amounts confer a health benefit on the host (FAO/WHO, 2001).…”
Section: Introductionmentioning
confidence: 99%